Fatores associados à hipertensão arterial em funcionários de uma Universidade Pública - Eduardo Caires Damasceno (2014)
The objective of this study was to analyze factors associated with hypertension (HTA). To this end, it was conducted an epidemiological, cross-sectional and analytical study, with 207 employees of the health campus of a public university in Belo Horizonte MG, Brazil. A questionnaire was applied to assess demographic, socioeconomic, anthropometric, lifestyle data and working conditions. The HTA was defined according to criteria proposed by the Brazilian Society of Hypertension: systolic blood pressure 140 mmHg and/or diastolic blood pressure 90 mmHg and/or use of antihypertensive medications. It was performed a statistical analysis in the following levels: descriptive (absolute and relative frequencies), bivariate (Pearsons chi-square test and Fisher's exact test) and multivariate (Poisson regression) with significance level set at 5% (p <0.05). The prevalence of HTA was 33.3% (95% CI: 27.0 to 40.2). Moreover, in our sample, assumed relevance the high prevalence of individuals with blood pressure above 130/85 mmHg - 47.8%, 95% CI: 40.9 to 54.9 - reference value that defines, according to National Cholesterol Education Program-Adult Treatment Panel III (NCEP-ATP III), the hypertension aiming at getting a diagnosis of metabolic syndrome. In the final model, after multivariate adjustment of data, males (PR: 1.93; CI 95%: 1.34-2.78), waist circumference [( 88 (female) 102 (male), RP: 1.85, 95% CI: 2.28 to 2.68)] and variable demand-control (active - high demand / high control; PR: 0.37, 95% CI: 0.19 to 0.73) remained independently associated with HTA. The prevalence of HTA was high and modifiable factors remained associated with this outcome, and it should be considered in discussions regarding actions for health promotion of the workers, focusing in the abdominal obesity and work conditions.